Financial Management Of UNISKA MAB Banjarmasin Students Influenced by Friends, Financial Education and Financial Literacy - Noor, Aris Setia; Kurniaty, Kurniaty; Rina, Rina (International Journal of Business, Law, and Education, 2025)
This study investigates the impact of peers, financial education, and financial literacy on the financial management practices of students at UNISKA MAB Banjarmasin. The research is based on the premise that the university years constitute a vital period for fostering financial independence. However, numerous students continue to lack the requisite skills for effective personal financial management. A quantitative methodology was adopted, with data collected via questionnaires administered to 150 respondents selected using the Slovin formula. Multiple linear regression analysis was performed to assess the relationships among the variables. The results indicate that peer influence exerts a negative, yet significant, effect on students’ financial management, implying that interactions with peers exhibiting excessive consumption habits may diminish financial discipline. Conversely, both financial education and financial literacy demonstrate positive, significant effects, with financial literacy identified as the more influential predictor. The study concludes that enhancing financial education and literacy is imperative for improving students’ financial behavior and ensuring long-term financial stability.